Peran Sistem Informasi Akuntansi Dalam Pemanfaatan Teknologi Terhadap Pembukuan Digital Pada UMKM Kampung Kue - Mukhamad Sholikudin; Anisa Lilatul Nikmah; Irda Agustin Kustiwi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This research evaluates the role of accounting information systems in harnessing technology for digital bookkeeping in MSMEs in Kampung Kue. These MSMEs still use manual bookkeeping, with the risk of missing records and potential fraud. The results suggest the adoption of digital bookkeeping applications as a solution, providing efficiency, transparency, and preventing recording errors. The application of this technology can help Kampung Kue MSMEs improve their financial management. Training and counseling are needed to ensure better understanding and acceptance from MSMEs of digital bookkeeping.